EXPLORING THE CORRELATION BETWEEN CORE SELF-EVALUATION AND EXERCISE INTENTION AMONG YOUTH IN RIVERS STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Core self-evaluation (CSE) is a fundamental personality trait that influences various aspects of an individual’s life, including their health behaviors. Understanding the relationship between CSE and exercise intention can provide insights into promoting healthier lifestyles among youth. This study aims to explore the correlation between core self-evaluation and exercise intention among youth in Rivers State, Nigeria. A cross-sectional survey was conducted from January to June 2024, involving 400 youth aged 18-25 years from different communities in Rivers State. Participants completed a structured questionnaire that included the Core Self-Evaluation Scale (CSES) and the Exercise Intention Scale (EIS). Data were analyzed using Pearson correlation and multiple regression analysis to determine the strength and nature of the relationship between CSE and exercise intention. The analysis revealed a significant positive correlation between core self-evaluation and exercise intention (r = 0.45, p < 0.01). Youth with higher CSE scores were more likely to have stronger intentions to engage in regular physical exercise. The regression analysis indicated that CSE accounted for 20% of the variance in exercise intention (R² = 0.20, p < 0.01). Factors such as self-esteem, self-efficacy, and emotional stability, which are components of CSE, were identified as significant predictors of exercise intention. The findings suggest that core self-evaluation plays a crucial role in shaping exercise intentions among youth in Rivers State. Interventions aimed at enhancing CSE, such as self-esteem and self-efficacy building programs, could be effective in promoting physical activity. Policymakers and health educators should consider incorporating CSE enhancement strategies into health promotion programs to foster a more active and healthy youth population.